Short-course aminoglycosides as adjunctive treatment in adults with sepsis: A post-hoc analysis of a prematurely terminated cluster randomized trial - Eva L. Koekenbier; Sharon E.J.D. van den Eijnde; Paul D. van der Linden; Jan Jelrik Oosterheert; Elske Sieswerda; Lisanne E.M. Vintcent; Linda M. Kampschreur; Hjalmar R. Bouma; Heidi S.M. Ammerlaan; Michelle Gompelman; Eefje Jong; Jan M. Prins; et al. (CMI Communications)
Background: Cephalosporin monotherapy or cephalosporin-aminoglycoside combination therapy are both used for empirical sepsis treatment in The Netherlands, with no evidence favouring either. We hypothesized that ceftriaxone or cefuroxime monotherapy is non-inferior to cefuroxime combined with gentamicin or tobramycin for empirical treatment of community-acquired sepsis. Methods: A cluster-randomized cross-over trial was conducted in nine Dutch hospitals, with a 1:1 randomization, comparing monotherapy to combination therapy in adults with severe community-acquired sepsis of unknown, suspected urinary tract or abdominal origin. The primary endpoint was 30-day all-cause mortality, with a non-inferiority margin of <5% adjusted absolute risk difference (aARD). Secondary endpoints included hospital re-admission and nephrotoxicity. The study stopped prematurely (before first cross-over) due to slow recruitment and 46% non-compliance to combination therapy. Patients treated with combination therapy (reference) and monotherapy were compared using logistic regression on multiple imputed data and propensity score overlap weighting for confounder adjustment. Results: Between May 2022 and May 2023, 451 patients were included; 158 received combination and 293 monotherapy. Thirty-day mortality was 11.4% (18/158) with combination therapy and 17.1% (50/293) with monotherapy, yielding an adjusted odds ratio (aOR) of 0.81 (95% CI:0.37–1.75) and an aARD of -2.8% (95% CI:-14.0–7.1). Nephrotoxicity incidence occurred in 11.9% (17/143) with combination therapy and 14.8% (38/256) with monotherapy (aOR 1.08, 95% CI:0.46–2.55). Conclusions: In an as-treated analysis, non-inferiority of monotherapy compared to combination therapy could not be demonstrated. The absolute risk difference for all-cause 30-day mortality was -2.8% and not statistically significant. Short-course aminoglycoside therapy was not associated with nephrotoxicity.